The Synergy between Teachers and Schools in Strengthening Inclusive Education Services in Elementary Schools in Kutai Kartanegara Regency - Yunita Purna Antari; Ferawati Vajrin; Choiriyah Widyasari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Inclusive education remains an important issue in ensuring equal learning opportunities for students with special needs in regular schools. This study aims to describe the implementation of inclusive education, focusing on the role of teachers, institutional support, and the supporting and inhibiting factors affecting inclusive services. This research employed a qualitative approach using interviews, observation, and documentation as data collection techniques. The findings show that teachers play a central role as planners, facilitators, mentors, motivators, social mediators, and evaluators in supporting students with special needs. Teachers adapt learning by simplifying instructions, reducing task complexity, providing additional time, using concrete and visual media, and giving individual assistance when needed. Institutional support is reflected in school policies that accept students with special needs, provide flexibility in learning, encourage teacher coordination, and maintain communication with parents. The study also found several supporting factors, including the principal’s commitment, teachers’ positive attitudes, peer acceptance, parental involvement, and flexible learning practices. However, inclusive education still faces obstacles such as limited teacher competence in special education, the lack of special assistant teachers, limited adaptive facilities, large class sizes, and unsystematic assessment and documentation of student progress. Therefore, inclusive education requires stronger collaboration, professional development, adaptive facilities, and systematic school-based support to ensure meaningful learning for all students.